Assessment of marine ecosystem health and its key influencing factors in Laizhou Bay, China - Wu, Wen; Hu, Jinming; Song, Dehai (Frontiers in Marine Science, 2023)
Introduction Major bays worldwide have been disturbed by human pressures to varying degrees in recent years, resulting in many ecological and environmental issues. Maintaining the health of the bay ecosystem has national and international significances, as it enhances the environmental regulation function and resource development value of the region. This study aims to examine the evolution trend and regulatory mechanism of ecosystem health in Laizhou Bay (LZB), China. Methods A comprehensive DPSIR-based indicator framework is established, comprising 40 representative indicators of the natural environment status, ecological service function, and social values of the LZB ecosystem. The subjective and objective integrated weighting method is applied to determine the indicator weight. The Ecosystem Health Index is then calculated to assess the LZB ecosystem health from 1980 to 2019 and key influencing factors are identified through the scenario analysis. Results The results show that the health status of the LZB ecosystem has fluctuated and then increased overall over the past 40 years, with a fairly healthy state in the 1980s, an unhealthy state in 2005, and then a rebound to a subhealthy state. The key factors affecting the LZB ecosystem health are mostly pressure items, with land-based pollution, particularly agricultural non-point source pollution, having a more significant impact than reclamations. Discussion Reasonable recommendations are finally put forward on improving the ecosystem health in the study area, including refining the legislation and integrated mechanism related to regional management, building a coordinated land-sea governance system and exploring new technologies for integrated marine management. This study fills the knowledge gap of ecosystem health assessment for the entire LZB in such a long-time scale, and the research outcomes are expected to provide scientific references and guidance for decision-making and social-economic sustainable development in LZB and other bays.